PENINGKATAN KETERAMPILAN DASAR MEMBACA PETA MENGGUNAKAN MODEL PROBLEM BASED LEARNING - Arief Budiman (Faculty of Teacher Training and Education, University of Lampung, 2017)
This research aimed to improve the basic skills of reading map by using problem based learning model. It is a classroom action reserach. The research activities were conducted into three cycles, each cycle consisted of planning, action, observation, and reflection, which aimed to improve the quality of learning. The subjects of this research were all of the students in the grade XII IPS 1 at MAN 1 Tanggamus in the academic year 2015/2016 with 32 students. The data collection instruments used are observation basic skill sheets of reading map. The data from the observation of each cycle become the basis or material improvement for the next cycle. In the first cycle the students who are good at reading map only 38%, in the second cycle the increase up to 59%, and in the third cycle they reached 84%. The results showed that using problem based learning model in teaching Geography has improvemed the basic skills of reading map.Penelitian ini bertujuan untuk meningkatkan keterampilan dasar membaca peta dengan menggunakan model pembelajaran problem based learning. Penelitian ini adalah penelitian tindakan kelas. Kegiatan penelitian ini dilaksanakan sebanyak tiga siklus, tiap siklus terdiri dari tahap perencanaan, tindakan, observasi, dan refleksi, yang bertujuan untuk memperbaiki kualitas pembelajaran. Subjek penelitian adalah seluruh siswa di kelas XII IPS 1 MAN 1 Tanggamus Tahun Pelajaran 2015/2016 sebanyak 32 siswa. Alat pengumpulan data menggunakan lembar pengamatan keterampilan dasar membaca peta. Data dari hasil observasi disetiap siklus menjadi dasar atau bahan perbaikan pada siklus berikutnya. Pada siklus pertama siswa yang terampil membaca peta hanya 38%, pada siklus kedua meningkat menjadi 59%, dan pada siklus ketiga mencapai 84%. Hasil penelitian menunjukkan bahwa terdapat peningkatan keterampilan dasar membaca peta setelah menggunakan model pembelajaran problem based learning dalam pembelajaran Geografi.Kata kunci: keterampilan dasar membaca peta, model pembelajaran problem based learning